Multiple congenital esophageal strictures masquerading as gastroesophageal reflux disease in an infant: a case report - Sharma, Yash P.; Sharma, Shruti; Surya, Mukesh; Kapila, Sumala (International Journal of Contemporary Pediatrics, 2023)
Congenital esophageal stenosis (CES) is a rare congenital disorder, generally presenting as vague complaints of dysphagia, vomiting and frequent respiratory complaints with symptoms usually appearing with introduction of complimentary feeding. We present the case of an eight-month-old male infant, presenting with regurgitation of feeds, recurrent episodes of cough and poor weight gain. He was diagnosed as a case of isolated multiple membranous esophageal strictures and underwent serial endoscopic esophageal dilatations which subsequently allowed him to swallow solid food and achieve good weight gain.